BOTS VS. AI. - Plummer-Fernandez, Matthew (Art in America, 2020)
The article reviews art exhibition "AI: More Than Human" to be held at the Forum, Groningen in Netherlands, through May 10, 2020 and featuring artificial intelligence artworks.